2017
DOI: 10.1136/emermed-2017-206647
|View full text |Cite
|
Sign up to set email alerts
|

The civilian validation of the Modified Physiological Triage Tool (MPTT): an evidence-based approach to primary major incident triage

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…When the performance of existing methods of triage such as the Major Incident Medical Management and Support (MIMMS) Triage Sieve and the UK Defence Medical Services (DMS) Military Sieve is analysed, it is evident that they do not accurately identify those in need of life-saving intervention 8 9. Indeed, this is not a problem unique to UK triage tools; both the START (USA) and Careflight (Australia) tools were found to be just as inaccurate following the London 7/7 bombings 10.…”
Section: The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…When the performance of existing methods of triage such as the Major Incident Medical Management and Support (MIMMS) Triage Sieve and the UK Defence Medical Services (DMS) Military Sieve is analysed, it is evident that they do not accurately identify those in need of life-saving intervention 8 9. Indeed, this is not a problem unique to UK triage tools; both the START (USA) and Careflight (Australia) tools were found to be just as inaccurate following the London 7/7 bombings 10.…”
Section: The Problemmentioning
confidence: 99%
“…Combining elements of civilian practice (the traditional MIMMS Triage Sieve) and the existing DMS Military Sieve, the NARU sieve now includes an assessment of conscious level and catastrophic haemorrhage 11 12. Unfortunately, a number of military and civilian trauma registry studies have shown that the Military Sieve (essentially analogous to the NARU sieve) also lacks the accuracy to adequately identify those needing a life-saving intervention 8 13…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were assumed to be non-ambulant due to the nature of the TARN database and its inclusion criteria. 6 Patients were defined as priority one (P1) if they had received one or more life-saving interventions from a previously defined list, derived through international consensus of experts involved in major incident management (Figure 1). 14 Using first recorded hospital RR in isolation, the sensitivity and specificity of the ≥24 breaths per minute threshold were compared with the existing threshold (≥22 breaths per minute) at predicting P1 status.…”
Section: Key Messagesmentioning
confidence: 99%
“…4 Derived specifically for this purpose, the Modified Physiological Triage Tool (MPTT) has shown the greatest sensitivity for predicting the need for lifesaving intervention, with the lowest rates of undertriage and acceptable levels of overtriage in both military and civilian populations. [5][6][7] Respiratory Rate (RR) and Glasgow Coma Scale (GCS) form key components of the MPTT and can both be time consuming to accurately measure,…”
Section: Introductionmentioning
confidence: 99%